Cassell's new French-English, English-French dictionary - Denis Girard; Gaston Dulong; Oliver Van Oss; Charles Guinness (London Cassell, 1963)
French-Canadian terms are included in this French dictionary which also affords a comprehensive coverage of classical literary language.
Keywords: French language -- Dictionaries -- English; English language -- Dictionaries -- French; Français (Langue) -- Dictionnaires anglais